Evidence-based supplements for the enhancement of athletic performance - Peeling, P.; Binnie, M. J.; Goods, P. S. R.; Sim, M.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
A strong foundation in physical conditioning and sport-specific experience, in addition to a bespoke and periodized training and nutrition program, are essential for athlete development. Once these underpinning factors are accounted for, and the athlete reaches a training maturity and competition level where marginal gains determine success, a role may exist for the use of evidence-based performance supplements. However, it is important that any decisions surrounding performance supplements are made in consideration of robust information that suggests the use of a product is safe, legal, and effective. The following review focuses on the current evidence-base for a number of common (and emerging) performance supplements used in sport. The supplements discussed here are separated into three categories based on the level of evidence supporting their use for enhancing sports performance: (1) established (caffeine, creatine, nitrate, beta-alanine, bicarbonate); (2) equivocal (citrate, phosphate, carnitine); and (3) developing. Within each section, the relevant performance type, the potential mechanisms of action, and the most common protocols used in the supplement dosing schedule are summarized. Abstract from author